UNDERSTANDING OF THE BATIK LAWEYAN SOLO CREATOR FOR COPYRIGHT (STUDY OF LAW NUMBER 28 OF 2014 CONCERNING COPYRIGHT) - Chandra Adi Mauli (Diponegoro Law Review, 2019)
The focus of the discussion in this study is the First Copyright Law as an embodiment of penetration of the legal culture of Western (capitalist) countries with individualistic nuances as positive law. Secondly, the culture of the laws of the local community where the Copyright Law is applied as a living law in society (Living law). The purpose of this paper is to know and explain not the implementation of the law as a positive law (positive law) in this case what is meant is the Copyright Act, in an Indonesian society and the Batik Laweyan craftsmen in particular, so that it is expected to explain why Copyright Law cannot function optimally in Indonesia which is marked by the many violations or piracy of a copyrighted work. The method in this writing is a qualitative method with the Sociological Research approach, while the paradigm used as the basis is the Paradigm of Social Definition with the aim of understanding social behavior through interpretation by explaining the path of development and its consequences according to its causes. Based on the social definition paradigm, the theory used is interactionism theory, which mainly emphasizes sociopsychological perspectives, the main goal of which is the individual in his personal personality and the interaction between internal opinion and one's emotions with social behavior. With the Symbolic Interaction Theory approach, in this study will be able to further reveal the behavior of certain community groups by interacting with existing social behavior. And also with the Phenomenology Theory is that human action becomes a social relationship if humans give a certain meaning or meaning to their actions, and other human beings also understand their actions as appropriate which means that humans are social beings, so that the awareness of daily life is an absolute magnification. As for the study findings it turns out, the Copyright Act in the application in the Laweyan Batik Craftsman community is in conflict with the Javanese legal culture that promotes harmony between neighbors, ewuhpekeweuh, tepasliro, mutual cooperation. If the law of copyright is strictly enforced, it will result in disturbance of neighborly living conditions. Because most Batik Laweyan craftsmen live next to each other even there is still a kinship, so that when it comes to demanding or monopolizing a work, it will lead to neighboring reluctance. They assume that even the art of batik is their property from the property of their ancestors so that anyone can imitate and make it.